Pedagogy into practice : a handbook for new teachers - Spielhagen, Frances R., 1946-; Speranzo, Nicole (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"The purpose of this book is to help new teachers transition from students in education courses to proactive educators who can translate what they have learned in methods classes into realistic practices as novice teachers. This book will help these candidates operationalize good educational pedagogy and understand the connections between theory and practice. This book will also explain the logical connections between standard curriculum theory and certification examinations like the edTPA"--